REVIEW OF ADSORPTION OF HEAVY METALS BY ADSORBENT MnFe2O4 – ZEOLITE IN WATER - Melinia, Luh Ayu; Naibaho, Marzuki; Puspita, Endah; Ramlan, Ramlan; Ginting, Masno (Indonesian Physical Review, 2023)
The existence of quality water on earth is essential for life and the consumption of existing living things. The problem of water pollution is a matter of great concern in world researchers' management of water resources. Heavy metals have a toxic effect on humans and the environment. This paper reviews the characteristics and methods of synthesis of MnFe2O4 and zeolite materials as adsorbents for removing heavy metal ions in water with critical properties such as surface area, magnetic properties, and adsorption capacity. We have collected data regarding the appropriate method for synthesizing MnFe2O4 and zeolite nano adsorbents. We have accumulated much data on the properties of MnFe2O4 and zeolite materials and the optimum adsorption capacity for heavy metal ions. Experimental factors such as pH, temperature, adsorption capacity, and ionic strength affecting metal ion removal have also been explored.